Studi Kasus: Deteksi African Swine Fever (ASF) dengan PCR (Polymerase Chain Reaction) pada Sampel Lapangan Babi dari Camplong, Kabupaten Kupang - Da Gama, Louisa Blandina; Gelolodo, Maria Aega (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
African swine fever (ASF) is a highly contagious hemorrhagic disease of pigs that threatens smallholder systems in Indonesia. We describe a field case from Camplong, Fatuleu Sub-district, Kupang Regency (East Nusa Tenggara) involving a 3.5-month-old male mixed Landrace–local pig reared under traditional management. Clinical history at the premises included anorexia, lethargy, tremors, diarrhea with hematochezia, and recent on-farm mortalities. Post-mortem examination noted a markedly darkened, enlarged spleen and renal petechiae. Basic hematology supported acute systemic viral infection. Splenic tissue was collected aseptically and tested by polymerase chain reaction (PCR), yielding a positive result for ASF; internal quality controls were acceptable. Concordant clinical, pathological, hematologic, and molecular findings support a definitive diagnosis of ASF in this case. At the population level, confirmation in Camplong indicates plausible local virus circulation and underscores the need for immediate risk communication, movement restriction, disinfection, strengthened biosecurity, and trace-back/trace-forward investigations among nearby smallholders. This case adds geographically contextualized evidence for ASF detection in resource-limited settings and illustrates the operational value of integrating field necropsy and confirmatory PCR on splenic tissue for timely decision-making. Findings may inform targeted surveillance and practical biosecurity guidance for smallholder pig producers in East Nusa Tenggara.